2015
DOI: 10.1371/journal.pone.0118205
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-cas Subtype I-Fb in Acinetobacter baumannii: Evolution and Utilization for Strain Subtyping

Abstract: Clustered regularly interspaced short palindromic repeats (CRISPR) are polymorphic elements found in the genome of some or all strains of particular bacterial species, providing them with a system of acquired immunity against invading bacteriophages and plasmids. Two CRISPR-Cas systems have been identified in Acinetobacter baumannii, an opportunistic pathogen with a remarkable capacity for clonal dissemination. In this study, we investigated the mode of evolution and diversity of spacers of the CRISPR-cas subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 45 publications
4
48
0
Order By: Relevance
“…Conversely, there were 319 centroids that were found only in the genomes of carbapenem-susceptible A. baumannii isolates compared to carbapenem-resistant A. baumannii isolates (see Table S5b). These centroids include genes involved in type IV secretion systems and CRISPR systems (59), as well as several transcriptional regulatory genes. In addition, 141 (44%) hypothetical genes, one transcriptional regulator, and many phage-related genes are included in this list.…”
Section: Ls-bsr Analysis By Location Of Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, there were 319 centroids that were found only in the genomes of carbapenem-susceptible A. baumannii isolates compared to carbapenem-resistant A. baumannii isolates (see Table S5b). These centroids include genes involved in type IV secretion systems and CRISPR systems (59), as well as several transcriptional regulatory genes. In addition, 141 (44%) hypothetical genes, one transcriptional regulator, and many phage-related genes are included in this list.…”
Section: Ls-bsr Analysis By Location Of Isolationmentioning
confidence: 99%
“…For example, the identification of the CRISPR genes in the susceptible isolates suggests the loss of these genes was an important step in acquiring genetic elements necessary for carbapenem resistance. CRISPR-cas systems provide bacteria a type of immunity against foreign genetic elements such as plasmids and bacteriophage; therefore, the loss of these genes may allow genetic elements to be acquired more readily (59).…”
Section: Ls-bsr Analysis By Location Of Isolationmentioning
confidence: 99%
“…Also, two CRISPR-Cas systems have been identified in some strains of A. baumannii (Di Nocera et al, 2011;Hauck et al, 2012). The AYE strain, whose genome is taken in many studies as the basis for GC1 studies (Touchon et al, 2014;Karah et al, 2015), and other A. baumannii clones were identified to harbor the subtype I-Fb, indicating potential interstrain horizontal transfer of this CRISPR-Cas system (Di Nocera et al, 2011;Karah et al, 2015). Based on distinct assortment of spacers harbored by each strain, a CRISPR-based sequence type (Schouls et al, 2003) identified a subclone of A. baumannii GC1 that it is likely it has been originated in Iraq and spread later to the United States and Europe (Karah et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Much of this work has focused on CRISPR-Cas9, but there are a large diversity of CRISPR types in bacterial genomes that are less well-characterized (67). The type I-Fa CRISPR-Cas system of A. baylyi is analogous to the type I-Fb CRISPR/Cas system of A. baumanii, except the cas1 gene appears last in the Cas operon (58,60). A. baylyi ADP1 contains three CRISPR arrays: one with 91 spacers adjacent to the Cas operon and two others with 21 and 6 spacers, respectively, located elsewhere in the genome.…”
Section: Discussionmentioning
confidence: 99%
“…The protospacer adjacent motif (PAM) for type I CRISPR-Cas systems has been reported to be a downstream GG dinucleotide (59), including for the subtype I-F system of Acinetobacter baumanii (60). This is equivalent to a CC located 5' of the spacer sequence on the strand that it matches in the target site DNA sequence.…”
Section: Multiple-gene-deletion Strainsmentioning
confidence: 99%